Relating Water Management Regimes and Rice Genotypes with Occurrence of Insect Pests and Diseases of Rice in Uganda - Awio, Thomas; Karungi, Jeninah; Bua, Bosco; Lamo, Jimmy (Journal of Global Agriculture and Ecology, 2016)
The research was conducted to assess the effect of water management regimes and/or rice genotypes on occurrence of insect pests and diseases of rice in Uganda. The study was conducted in phased field trials under natural conditions during the second rainy season of 2012 and the first rainy season of 2013. The trials were laid out in a Randomised Complete Block Design arranged as a split plot with three replications. Water management regimes (alternate wetting and drying-AWD, continuous flooding-CF and continuous drying-CD) constituted the main-plots and rice genotypes the sub-plots. Results indicated that the stalked-eyed fly (Diopsis spp) and African rice gall midge (Orseolia oryzivora) were the most encountered insect pests and both pests occurred highest in CF fields. Rice blast, brown spot, grain rot, rice yellow mottle virus (RYMV) and sheath rot were the diseases recorded in rice during the study. Rice blast and brown spot were the most prevalent diseases (>10% incidence), and brown spot was most prevalent under the AWD regime whereas RYMV was most prevalent in the CF regime. The level of occurrence of rice blast and RYMV recorded in the different water management regimes was dependent on the rice genotype. Generally, different genotypes had different insect pest/diseases occurrence profiles. The implication of these findings therefore is that for effective integrated pest management, knowledge of the most limiting pest/disease is important in deciding the appropriate water management regime. However, further experimental trials need to be conducted in different agro-ecological zones to verify these findings.
Keywords: Alternate wetting and drying; Rice genotypes; Disease incidence and severity